Waist-To-Hip Ratio Predicts Abnormal Overnight Oximetry in Men Independent of Body Mass Index - Bock, Joshua M.; Rodysill, Kirk J.; Calvin, Andrew D.; Vungarala, Soumya; Sahakyan, Karine R.; Cha, Stephen S.; Svatikova, Anna; Lopez-Jimenez, Francisco; Somers, Virend K. (Frontiers in Cardiovascular Medicine, 2021)
Background: Ambulatory overnight oximetry (OXI) has emerged as a cost-effective initial test for sleep disordered breathing. Obesity is closely associated with obstructive sleep apnea (OSA); however, whether body mass index (BMI) or waist-to-hip ratio (WHR) predicts abnormal overnight OXI remains unknown. Methods: We performed a retrospective cross-sectional study of 393 men seen in the Executive Health Program at Mayo Clinic in Rochester, Minnesota who underwent ambulatory overnight OXI ordered by preventive medicine physicians between January 1, 2004 through December 31, 2010. We compared participant/spouse-reported symptoms (sleepiness, snoring), physician indications for OXI (obesity, fatigue), Epworth Sleepiness Scale scores, anthropomorphic measurements (WHR, BMI), and comorbid medical conditions (hypertension, diabetes) with OXI results. Results: 295 of the 393 men who completed OXI had abnormal results. During multivariate analysis, the strongest independent predictor of abnormal OXI for men was WHR (≥1.0, OR=5.59) followed by BMI (≥30.0kg/m2, OR=2.75), age (≥55yrs, OR=2.06), and the presence of snoring (OR=1.91, P<0.05 for all). A strong association was observed between WHR and abnormal OXI in obese (BMI≥30.0kg/m2, OR=6.28) and non-obese (BMI<29.9kg/m2, OR=6.42, P<0.01 for both) men. Furthermore, 88 men with abnormal OXI underwent polysomnography with 91% being subsequently diagnosed with OSA. Conclusions: In ambulatory, predominantly middle-aged men undergoing preventive services evaluation many physician indications for OXI were not predictors of abnormal results; however, WHR strongly predicted abnormal OXI in obese and non-obese men. As such, we suggest middle-aged men who snore and have a WHR≥1.0 should be directly referred to a sleep clinic for polysomnography.